(untitled) (Ameghiniana, 2026)
Seven fossil woods recovered from the fossiliferous localities of Concordia and Santa Ana (Entre Ríos Province, Argentina), corresponding to the El Palmar Formation (Late Pleistocene), were analysed. This unit is an important source of information on the climatic and ecological events that occurred towards the end of the Quaternary (MIS5 and MIS7) in the middle basin of the Uruguay River, Southeastern South America. The features of the tracheids and their pits in the radial walls, the cross-fields with cupressoid-type pits, and axial parenchyma allow their assignment to Podocarpoxylon. However, detailed observations such as the amount of diffuse axial parenchyma with smooth transverse end walls, uniseriate contiguous and non-contiguous intertracheal pits in the radial walls, and cross-fields with one or two pits, allow it to be related to the modern species Podocarpus lambertii. This species grows in the Atlantic forests of South America. Based on the preservation of fossil material and direct observations of modern specimens, we erected Podocarpoxylon paralambertii sp. nov. Paleodendrochronological analysis shows that the fossils had an evergreen habit, with an estimated trunk diameter greater than 50 cm. The growth-ring type D suggests that the specimens grew in a non-seasonal or weakly seasonal environment. The presence of the Podocarpaceae fossils in the El Palmar Formation indicates that the distribution of this family was more widespread in South America in the past.